Matuto, Magbasa, Maglaro: Learning to read braille through play. - Lopez MASc, Rhianne M.; Pinder PhD, Shane D.; Davies PhD, T. Claire (Assistive Technology, 2021)
In September 2016, Digital Learning for Development and All Children Reading released a "Grand Challenge for Development" urging researchers to explore the barriers that children with sensory disabilities in the Philippines face with respect to learning how to read. We sought to address one component of this challenge; engagement of persons with visual impairment in learning how to read in braille. The primary goal of this study was to engage in the co-design process to create a device to help young children with visual impairments learn to identify letters and short words in braille as a first step to reading. Participant questionnaires identified barriers of current reading devices including: accessibility, portability, durability, usability, and function. A design was prototyped based on results from a weighted evaluation matrix and feedback from partners who taught reading to persons with visual impairments. Usability testing showed that the device was easy to use and interactive. Suggestions for improvement included adding various learning modes and reducing the size, weight, and cost of the device. Results from this study highlight advantages of engaging in the co-design process and provide important data for other researchers developing devices for persons with visual impairments.